Preparing for Future Droughts in Lima, Peru : Enhancing Lima’s Drought Management Plan to Meet Future Challenges - Groves, David G.; Bonzanigo, Laura; Syme, James; Engle, Nathan L.; Rodriguez Cabanillas, Ivan (World Bank, Washington, DC, 2019)
Lima is the capital of and largest city in Peru, with an estimated population of about 10 million people. SEDAPAL, Lima’s water utility, provides water to most of the metropolitan region. While SEDAPAL is generally able to meet the current needs of its customers and respond effectively to most drought conditions that have been experienced in the past, it faces a number of challenges doing so in the future. A rapidly growing population and expanding city will likely increase demand. Currently available surface and groundwater supplies that SEDAPAL relies on are also just adequate to meet current needs. Changes in these supplies would challenge SEDAPAL’s ability to manage drought conditions. This study evaluates the performance of SEDAPAL’s current drought management plan against future droughts and proposes augmentations. This study takes a deeper look into the operation of the system, the different triggers, other possible augmentations than those related to increasing supply. The audience of this report includes SEDAPAL and stakeholders from Lima as well as other water managers and researchers interested in drought management planning methodologies and case studies. This study is novel, as it uses methods for Decision Making Under Deep Uncertainty to explore uncertainty in near-term drought management conditions and identify drought management strategies robust to these uncertainties